Karakteristik Personal Sebagai Moderasi Hubungan Pelatihan UMKM dan Orientasi Kewirausahaan - Salix Fini Maris; Aji Hermawan; Siti Jahroh (Universitas Airlangga, 2020)
Entrepreneurship training helps to support culture and entrepreneurship by changing mindsets and increasing expertise. Micro, Small and Medium Enterprises (MSMES) training program has a challenge to pay more attention to the personal characteristics of entrepreneur to make it effective. Personal characteristics affect the training process, which is generate training success by obtaining satisfaction of the participants. The study examines personal characteristics; learning motivation, personal targets, and extraversion personality, as aspects that influence relationship between training and entrepreneurship orientation. The study was conducted on entrepreneur that took part in entrepreneurship training program using questionnaires. The results of the questionnaire were analyzed with the SEM PLS model and generate results of the study, thus personal characteristics as moderation have no significant influence or relationship to the strength of the relationship between training and entrepreneurial orientation. Even though same as training, personal characteristics have a direct attachment to entrepreneurial orientation. The results of this study can be a reference for the implementation of the training to stimulates the trainees' personal characteristics to support entrepreneurial orientation.